Recruit to reject? Harvard and African American applicants. (June 2022) - Arcidiacono, Peter; Kinsler, Josh; Ransom, Tyler
Abstract: Elite colleges in the US have seen dramatic increases in applications over the past few decades, in part the result of expanded applicant recruiting. However, broadening the applicant pool while also maintaining diversity may require encouraging applications from individuals who have little to no chance of admission. We shed new light on this behavior using detailed data on Harvard University that was made public as part of the SFFA v. Harvard lawsuit. We show that Harvard encourages applications from many students who effectively have no chance of being admitted, and that this is particularly true for African Americans. After a 28-year period where the African American share of applicants to Harvard was roughly stable, the African American share of applicants grew by almost 57% over four years. Yet, there was little change in the share of admits who were African American, consistent with our finding that the increase in applications was driven by those with lower SAT scores. We show that this change in applicant behavior resulted in substantial convergence in the overall admissions rates across races yet no change in the large cross-race differences in admissions rates for high-SAT applicants.